2014
DOI: 10.18553/jmcp.2014.20.7.691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adherence and Weight Loss on Glycemic Control in Patients with Type 2 Diabetes: Cohort Analyses of Integrated Medical Record, Pharmacy Claims, and Patient-Reported Data

Abstract: BACKGROUND: Managed care organizations put great effort into managing the population of patients with type 2 diabetes mellitus (T2DM) because of the health and economic burden of this disease. In patients with T2DM, weight loss and glycemic control are primary treatment aims to help improve patient outcomes, but these goals are not easily achieved. While achieving these aims requires a multifaceted approach of drug therapy management and lifestyle modification, truly understanding the role of medication adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 42 publications
(36 reference statements)
5
55
0
1
Order By: Relevance
“…Fifthly, we used the inclusion criteria published in 1989 but not the updated version published in 2010. Finally, it needs to be noted that MARS-5 has not been commonly used in the neurology clinic because of its ineffectiveness in patients with 'silent' disease, such as hypertension, COPD, and type 2 diabetes mellitus [18,19,44,45]. However, the drive of medication adherence is stronger in patients with epilepsy in order to manage their seizures' symptoms; therefore, they tend to provide more accurate self-reported MARS-5 results.…”
Section: Discussionmentioning
confidence: 99%
“…Fifthly, we used the inclusion criteria published in 1989 but not the updated version published in 2010. Finally, it needs to be noted that MARS-5 has not been commonly used in the neurology clinic because of its ineffectiveness in patients with 'silent' disease, such as hypertension, COPD, and type 2 diabetes mellitus [18,19,44,45]. However, the drive of medication adherence is stronger in patients with epilepsy in order to manage their seizures' symptoms; therefore, they tend to provide more accurate self-reported MARS-5 results.…”
Section: Discussionmentioning
confidence: 99%
“…Our search returned 542 unique articles/abstracts, among which nine journal articles and six abstracts were selected. Most of the articles were excluded because they did not investigate drug effectiveness or safety ( n = 350), some for using only EHR ( n = 47) or claims data ( n = 10), some for using both types of datasets without data linkage ( n = 55).…”
Section: Existing Literature On Linking Ehr To Claims Data To Study Dmentioning
confidence: 99%
“…If not, the researcher will need to supplement the data with EHR. Some example outcomes in this scenario include change in glycosylated hemoglobin (HbA1c), BMI, or blood pressure (BP), smoking cessation, semen volume and sperm concentration, left ventricular ejection fractions assessed by an echocardiogram, or QT interval prolongation assessed by an electrocardiogram. When choosing EHR as the additional source of outcome information, researchers should be mindful of how the information was recorded and how patients with the outcome information recorded in EHR differ from those missing such information.…”
Section: Considerations For Linking Databasesmentioning
confidence: 99%
“…Continuing treatment with antidiabetes medication, irrespective of treatment class, is known to positively influence outcomes. Numerous recent studies have reported associations between persistence/adherence and glycemic control, resource use, mortality, and cost, in patients with T2D 2328 . Our results suggest that policy makers should consider implementing interventions targeted to increase persistence to RAI, which may translate into better outcomes.…”
Section: Discussionmentioning
confidence: 99%